Metabolomic analysis of rumen fluid in Tan sheep reveals sex-specific key metabolites and pathways associated with residual feed intake - ChengLei Song; Dongqian He; Zhuo Yang; Yu Fu; Hao Zheng; Zhou Xing; Wenjuan Shen; An Shi; Jinzhong Tao (Scientific Reports)
Abstract Improving feed efficiency is a key factor in the sustainable development of the livestock industry. Livestock breeds with the low residual feed intake (RFI) trait can reduce feeding costs and increase economic benefits. The rumen metabolome is a pivotal variant affecting ruminant feed efficiency, but current research often ignores sex effects on both. The dynamic changes in rumen metabolites in male and female sheep with different RFI were studied to reveal the sex-specific metabolites and pathways related to feed efficiency. By recording the initial body weight, final body weight, and dry matter intake of 345 Chinese Tan sheep, 14 (male: female = 1:1) with extremely low RFI and 16 (male: female = 1:1) with extremely high RFI were selected for non-targeted metabolomics analysis of rumen fluid. Among the 610 metabolites identified, N-acetylneuraminic acid, isoamylamine, and punicic acid had greater content in female sheep with low RFI (AUC > 0.7). In comparison, 29 metabolites had greater content in the rumen fluid of male sheep, including malic acid and 17% free fatty acids. And they were enriched in riboflavin metabolism, linoleic acid metabolism, pyrimidine metabolism, and histidine metabolism pathways. The results show that sex affects rumen metabolism and the RFI trait. Given differential metabolite function studies, male sheep may rely on greater concentrations of malic acid and B vitamins to participate in the tricarboxylic acid cycle and achieve higher energy utilization efficiency. These findings provide insights into the differences in rumen metabolites linked to the RFI trait and sex differences in sheep.